Clinical misconceptions and diagnostic delays in extrapulmonary tuberculosis: an evaluation on 89 cases - Gürcüoglu, Emel (The Journal of Infection in Developing Countries, 2025)
Introduction: Extrapulmonary tuberculosis (EPTB) has highly variable clinical findings, and has a more difficult diagnostic process than pulmonary tuberculosis (PTB). The aim of this study was to examine the difficulty of the diagnostic process in 89 cases that applied to different clinics in our hospital, with different complaints. Methodology: A total of 89 patients diagnosed with EPTB between March 2020 and March 2024 were included in the study. EPTB diagnosis was determined by excluding patients with primary PTB. Results: The mean age of the cases was 47.84 ± 19.23 years, and 52 (58.4%) of the patients were women. There was a significant relationship between the affected area and gender (p < 0.001). The rate of peripheral lymphadenopathy (LAP) involvement was much higher in women than that in men (85.2% vs. 14.8%). Pleural involvement was 6.5-fold higher in men than in women (51.4% vs. 7.8%). There was also a significant relationship between the affected area and the time to diagnosis (p < 0.001). While peripheral LAP cases were diagnosed late, patients with pleural involvement were diagnosed more quickly (p < 0.001). The rate of smoking addiction was high in males with pleural involvement (79.9%). Quinolone use was 77.4% in the early-diagnosed group and 54.9% in the late-diagnosed group (p = 0.110). Conclusions: Due to the difficulty of diagnosis, EPTB should be included in the differential diagnoses of all relevant medical specialties, and insistence should be made for the diagnosis in the presence of clinical suspicion.